Feasibility of business expansion in the seed industry - Lukach, Sarah Elizabeth (Kansas State University, 2017)
The landscape of the United States seed industry has changed substantially over the last 100 years. In the mid-1930s, there were 115 active seed corn companies marketing seed in the United States. By the 1980s, there were 303 hybrid seed corn companies and in 2016 there were 140 active hybrid seed corn companies in the United States. As the seed industry continues to evolve, so will the logistics and methods of which seed is sold to farm customers. The purpose of this thesis is to analyze and determine if a seed business expansion provides a positive net present value and rate of return for the management based on the capital costs of the investment and estimated income opportunities. Based on historical information of the existing business and the new market territory opportunities, a ten year projected cash flow was estimated to provide a basis for the net present value and internal rate of return analysis. Sensitivity analysis was applied to different variables in the cash flow model to identify variables of risk and the impact on the projected cash flow and net present value analysis. The projected cash flow model and net present value analysis provides management a basis for the decision to expand their existing business. The conclusion of the net present value and internal rate of return analysis was that the expansion of the seed business was profitable under most sensitivity scenarios. Recommendations were made for additional research that could be performed to maximize and diversify the business’s product offerings and net income.
Keywords: Feasibility; Net present value; Business expansion; Agriculture- economics